Stress drop analysis of earthquakes in the vicinity of Ayvacık geothermal reservoir - Yıldıran, Eda. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2023., 2023)
An earthquake swarm occurred in Çanakkale-Ayvacık, where started with an earthquake of M=5.4 magnitude on February 6, 2017, and more than 4000 earthquakes were recorded in 2 months. A significant number of these earthquakes were larger than Mw = 4. Most of the activity occurred on the southwest-dipping Tuzla Fault, which is a normal fault with WNW strike. Given that the fault region is a geothermal reservoir where active geothermal power plants operate, it is important to examine the characteristics of these earthquakes more closely. The activity started near a geothermal power plant and expanded along the Tuzla fault. In this thesis, the stress drops of earthquakes that occurred in the Ayvacık Region during the 2017 earthquake swarm was studied. Stress drop is a crucial macroscopic parameter for earthquakes and in geothermal regions, and variations in stress drop might indicate changes in stress conditions, especially pore pressure. The corner frequencies of 106 earthquakes with magnitudes greater than ML ≥ 3.0 were calculated from the P waveforms using 2 stations in the vicinity of the activity. We also calculated the moment magnitudes of 139 earthquakes with local magnitudes greater than 2.8 using P wave spectra. Our analysis shows that the stress drop of the earthquakes before and during the 2017 activity is quite variable. In addition, in comparison to the earthquakes that occurred before (∼ 3 MPa), the average stress drop is higher with mean values of about 7 − 9 MPa. We infer that the higher average stress drop during the 2017 activity might be related to a change in the pore pressure, where an increase in pore pressure might have led to a decrease in effective normal stress leading to higher slip values and therefore higher stress drops.
Keywords: Earthquakes -- Ayvacık -- Turkey.; Seismology -- Data processing.; Seismology -- Statistical methods.; Geothermal resources.